ESA1 regulates meiotic chromosome axis and crossover frequency via acetylating histone H4. Issue 16 (20th August 2021) - Wang, Ying; Zhai, Binyuan; Tan, Taicong; Yang, Xiao; Zhang, Jiaming; Song, Meihui; Tan, Yingjin; Yang, Xuan; Chu, Tingting; Zhang, Shuxian; Wang, Shunxin; Zhang, Liangran
Abstract: Meiotic recombination is integrated into and regulated by meiotic chromosomes, which is organized as loop/axis architecture. However, the regulation of chromosome organization is poorly understood. Here, we show Esa1, the NuA4 complex catalytic subunit, is constitutively expressed and localizes on chromatin loops during meiosis. Esa1 plays multiple roles including homolog synapsis, sporulation efficiency, spore viability, and chromosome segregation in meiosis. Detailed analyses show the meiosis-specific depletion of Esa1 results in decreased chromosome axis length independent of another axis length regulator Pds5, which further leads to a decreased number of Mer2 foci, and consequently a decreased number of DNA double-strand breaks, recombination intermediates, and crossover frequency. However, Esa1 depletion does not impair the occurrence of the obligatory crossover required for faithful chromosome segregation, or the strength of crossover interference. Further investigations demonstrate Esa1 regulates chromosome axis length via acetylating the N-terminal tail of histone H4 but not altering transcription program. Therefore, we firstly show a non-chromosome axis component, Esa1, acetylates histone H4 on chromatin loops to regulate chromosome axis length and consequently recombination frequency but does not affect the basic meiotic recombination process. Additionally, Esa1 depletion downregulates middle induced meiotic genes, which probably causing defects in sporulation and chromosome segregation.